2010
DOI: 10.1159/000311522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin II on Renal Dopamine Metabolism: Synthesis, Release, Catabolism and Turnover

Abstract: Background/Aims: Dopamine (DA) uptake inhibition in the renal cortex, elicited by angiotensin II (ANG II), is mediated by AT1 receptors and signals through the phospholipase C pathway and activation of protein kinase C and CaM-kinase II. By this indirect way, ANG II stimulates renal Na+,K+-ATPase activity through DA intracellular reduction. In the present work, we continued to study different aspects of renal DA metabolism in DA-ANG II interaction, such as DA synthesis, release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 68 publications
1
15
0
2
Order By: Relevance
“…Por otro lado, se ha descripto que la Ang II inhibe la captación renal de DA mediante estimulación de los receptores AT 1 , en un mecanismo que implica la vía de señalización de PLC, con generación de los segundos mensajeros inositol 1,4,5-trifosfato (IP3) y diacilglicerol (DAG), liberación de Ca 2+ intracelular y activación de PKC y calmodulina quinasa II (CaMKII) (Choi y col., 2006;Choi y col., 2009). Adicionalmente, la Ang II reduce la actividad de la DCAA y estimula la actividad de la MAO, reduciendo la síntesis y aumentando el catabolismo de la DA renal (Choi y col., 2010). En su conjunto, todos estos efectos previenen la acumulación de DA en las células del TP, resultando en una disminución de la biodisponibilidad de la amina en el interior de la célula y en la luz tubular de la nefrona.…”
Section: Interacción Entre El Sistema Renina Angiotensina Y El Sistemunclassified
“…Por otro lado, se ha descripto que la Ang II inhibe la captación renal de DA mediante estimulación de los receptores AT 1 , en un mecanismo que implica la vía de señalización de PLC, con generación de los segundos mensajeros inositol 1,4,5-trifosfato (IP3) y diacilglicerol (DAG), liberación de Ca 2+ intracelular y activación de PKC y calmodulina quinasa II (CaMKII) (Choi y col., 2006;Choi y col., 2009). Adicionalmente, la Ang II reduce la actividad de la DCAA y estimula la actividad de la MAO, reduciendo la síntesis y aumentando el catabolismo de la DA renal (Choi y col., 2010). En su conjunto, todos estos efectos previenen la acumulación de DA en las células del TP, resultando en una disminución de la biodisponibilidad de la amina en el interior de la célula y en la luz tubular de la nefrona.…”
Section: Interacción Entre El Sistema Renina Angiotensina Y El Sistemunclassified
“…Similarly, short-term treatment with AngII diminishes D 1 R at the plasma membrane in the WKY, but not SHR, although chronic treatment results in increased D 1 R expression (37), possibly as compensation. AngII also decreases dopamine uptake and dopamine synthesis in the renal cortex (38). Simultaneous activation of D 1 R and AT 1 R can increase or decrease Na + ,K + -ATPase activity that is dependent on the intracellular sodium concentration, an increase of which favors D 1 R action (39).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most investigated subjects related to the pathophysiology of DN is the renin-angiotensin system. Regardless of their hemodynamic effects, it has been reported that Ang II contributes to the development and progression of renal damage through the AT1 receptor in diabetic patients [17][18][19][20]. The activity of monoamine oxidases, especially MAO-A, is increased by Angiotensin II through the AT1 receptor in kidneys [21].…”
Section: Correlation Between Renal Function Parameters and Oxidant Anmentioning
confidence: 99%
“…In addition, Angiotensin II increases MAO activity in rat kidneys by activating AT1 receptor. Diabetic animal models, clinical trials, and meta-analysis have clearly demonstrated the effectiveness of angiotensin-converting enzyme inhibitors or angiotensin receptor blockers to improve glomerular and tubulointerstitial damage, reduce proteinuria, and decrease progression of chronic kidney disease [18][19][20][21]. According to the above description, MAO levels might be found increased in DN and this state might contribute to reducing the natriuretic effect of dopamine and to unbalanced cell redox state.…”
Section: Introductionmentioning
confidence: 99%